2010
DOI: 10.1007/s00216-010-4152-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methotrexate and its eight metabolites in cerebrospinal fluid by solid-phase extraction and triple-stacking capillary electrophoresis

Abstract: We establish a triple-stacking capillary electrophoresis (CE) separation method to monitor methotrexate (MTX) and its eight metabolites in cerebrospinal fluid (CSF). Three stacking methods with different mechanisms were combined and incorporated into CE separation. Complete stacking and sharp peaks were achieved. Firstly, the optimized buffer (60 mM phosphate containing 15% THF and 100 mM SDS) was filled into the capillary, which was followed by the higher conductivity buffer (100 mM phosphate, 2 psi for 45 s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Cheng et al . () reported triple‐stacking capillary electrophoresis for analysis of methotrexate and its eight different metabolites in cerebrospinal fluid. The buffer system chosen was 60 m m phosphate, pH 3.0 containing 15% Tetrahydrofuran (THF) and 100 m m SDS.…”
Section: Analyses Of Anticancer Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et al . () reported triple‐stacking capillary electrophoresis for analysis of methotrexate and its eight different metabolites in cerebrospinal fluid. The buffer system chosen was 60 m m phosphate, pH 3.0 containing 15% Tetrahydrofuran (THF) and 100 m m SDS.…”
Section: Analyses Of Anticancer Drugsmentioning
confidence: 99%
“…At this stage, the samples were ready to load onto the CE machine. Cheng et al (2010) reported SPE and triple-stacking CE for analysis of methotrexate and its eight different metabolites in cerebrospinal fluid. The blood samples were denatured by adding perchloric acid followed by vortex and centrifugation.…”
Section: Sample Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al combined three stacking techniques, including LVSS, dynamic pH junction, and sweeping for analysis of methotrexate (MTX) and its eight metabolites in whole blood by MEKC, and about 40‐fold sensitivity increase was attained compared with that the single CZE mode. Cheng et al also adopted such triple‐stacking CE mode to monitor MTX and its eight metabolites in cerebrospinal fluid (CSF). The LODs (hydrodynamic injection 2 psi, 99.9 s) were observed to be 0.1 μM for MTX, 7‐OHMTX, MTX‐(Glu) n , n = 2–5 and 0.2 μM MTX‐(Glu) 6 , and 0.3 μM for DAMPA and MTX‐(Glu) 7 .…”
Section: Ce On‐line Stackingmentioning
confidence: 99%
“…We used the HPLC-PDA/FTICR-MS method to screen for impurities in MTX drug substances produced by different manufacturers. The proposed formulae of the parent ions, the observed and calculated masses, and the measurement error for the 15 detected impurities (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and the MS n product ions are summarized in Table 2. The MS n spectra and their assignments are shown in the online Supporting information.…”
Section: Identification Of 15 Impurities In Mtx Drug Substancesmentioning
confidence: 99%